THE TRAINING OF THE FUTURE TEACHERS OF HISTORY TO ETHOCULTRAL ACTIVITY IN THE SOUTH OF UKRAINE: THE RESULTS OF EXPERIMENTAL WORK - Bigunova, Yuliya V. (Educological discourse, 2015)
The author of the article analyses the process of shaping professional pedagogical readiness of future teachers of history for activity of multicultural space in the South of Ukraine, the essence of ethnocultural activity of the experts and to determining a set of psychological-pedagogical conditions. The author gives the statistical data on results of the experimental work to form preparation of future teachers of history to ethnocultural activity.